Lifestyle and metabolic factors affect risk for meningioma in women: a prospective population-based study (The Cohort of Norway) - Gheorghiu, Anamaria; Brunborg, Cathrine; Johannesen, Tom B.; Helseth, Eirik; Zwart, John-Anker; Wiedmann, Markus K. H. (Frontiers in Oncology, 2024)
Meningioma is the most common primary brain tumor, with a clear preponderance for women. Obesity is considered a risk factor for development of meningioma. Obesity is also the clinical hallmark of metabolic syndrome, characterized by glucose intolerance, dyslipidemia and hypertension. Life style and metabolic factors directly impact on overweight and obesity and are therefore potential risk factors for meningioma development. The aim of this study is to assess life-style and metabolic factors for meningioma risk in women.: The Cohort of Norway (CONOR) is a nationwide health survey, conducted between 1994 and 2003, including anthropometric measures, blood tests and health questionnaires. Linkage to the National Cancer Registry enabled identification of intracranial meningioma during follow-up until December 2018.Results: 81 652 women were followed for a total of 1.5 million years and 238 intracranial meningiomas were identified. Increasing level of physical activity (HR 0.81; 95% CI 0.68-0.96; p trend <0.02) and parity (HR 0.83; 95% CI 0.71-0.97; p trend <0.03) were negatively associated with meningioma risk. Diabetes mellitus or glucose intolerance increased the risk for meningioma (HR 2.54; 95% CI 1.60-4.05). Overweight and obesity were not associated with meningioma risk, neither was metabolic syndrome. However, participants without metabolic dysfunction had a reduced meningioma risk, while participants with all 5 metabolic factors present, had a 4-fold risk increase for meningioma (HR 4.28;).Life-style factors seem to influence meningioma risk significantly. However, detangling the complex associations and interactions between factors for meningioma risk will be a challenging task for future studies.